Transparency in Government Governance by the Head of Bubalango Village, East Sumalata District, North Gorontalo Regency - Dunggio, Nelsin; Gobel, Lisda Van; Nggilu, Rukiyah (Indonesian Journal of Advanced Research, 2023)
This research aims to determine the transparency of government governance by the Head of Bubalango Village, East Sumalata District, North Gorontalo Regency. The focus in this research is fairness, accountability, and professionalism. The research method uses a descriptive qualitative approach. Data collection techniques were carried out through in-depth interviews with a number of informants, observation and recording secondary data related to the research problem. The results of the research concluded that, fairness does not yet exist completely because village governance has not been implemented well as in policies perceived by the community, accountability in governance does not run in accordance with village legislation, where in terms of responsibility for workers or errors by officials other villages and professionals in government governance in Bubalango Village are not yet owned by village officials or village governance has not been optimally carried out by village officials in providing excellent service to the community so that the community gets comfort and good service provided by the Bubalango Village District government East Sumalata, North Gorontalo Regency.